Validation of the Italian version of the Kagan scales for people with aphasia and their conversation partners. Issue 3 (4th March 2019) - Muò, Rossella; Rinaudo, Marta; Rabino, Giulia; Massari, Ermelinda; Schindler, Antonio; Steni, Patrizia; Iacomussi, Tiziana
ABSTRACT: Background : The importance of conversation partners (CPs) for persons with aphasia (PwA) was recently highlighted. Trained CPs are shown to increase communicative access and improve quality of life. The Kagan scales, i.e., "Measure of skills in Supported Conversation" and "Measure of Participation in Conversation" (the MSC-MPC scales), between PwA and their CPs were designed to assess the communication dyad. The MSC-MPC scales were translated and adapted to Italian in 2015. Aim : To validate the Italian version of the MSC-MPC scales (I-MSC/MPC) by assessing intra- and inter-rater reliability and concurrent validity. Methods & Procedures : Thirty-two couples formed by 16 PwA and two CPs (one trained and one untrained) for each PwA were enrolled in the study. Aphasia severity was staged by the Therapy Outcome Measures "Dysphasia" impairment scale. Functional communication and pragmatic abilities were assessed with the I-ASHA-FACS and the Pragmatic Protocol, respectively. The PwA were videotaped while communicating both with trained and untrained CPs. All videotapes were assessed using the I-MSC/MPC scales by one expert speech and language therapist and two trainee speech and language therapists. The Intraclass Correlation Coefficient (ICC) was used to calculate inter- and intra-rater reliability. Correlations between the I-MSC/MPC scales and the aphasia severity, the I-ASHA-FACS, and the Pragmatic Protocol results were calculated by the Spearman's test. The Mann-Whitney test was used to separate the I-MSC/MPC results obtained by the trained CPs from the untrained CPs. Outcomes & Results : Inter-rater and intra-rater reliability ICC results were highly significant and strong (ICC > .906, ICC > .978, p < .001, respectively). Significant correlations between the aphasia severity and the I-MSC/MPC scales ranged from moderate to strong (Spearman rho>.487, p < .005). Correlations between the I-MSC and the I-ASHA-FACS domains ranged from moderate to strong (rho >.458, p < .008). Correlation between the I-MPC and the I-ASHA-FACS domains were generally strong (rho > .569, p < .001) while correlations between the I-MSC and the I-ASHA-FACS domains ranged from moderate to strong (rho > .458, p = .008). Pragmatic aspects were shown to be mostly preserved in the PwA. All correlations between the I-MSC/MPC scales and the Pragmatic Protocol were strong (rho >.635, p < .008). The Mann-Whitney test showed significant results for the I-MSC scale ( p < .026). Conclusions : The I-MSC-MPC scales proved to be a valid and reliable instrument to assess the communicative dyad. The I-MSC scale was also used to distinguish trained from untrained CPs. The use of I-MSC-MPC scales is recommended in clinical practice.